New processing research on sheet metal bidirectional pressure forming using a magnetorheological fluid. Issue 1 (January 2017) - Li, Feng; Zhou, Fu; Wang, Mo; Zhu, Shu; Jin, Cheng
Abstract In order to break through the technical bottlenecks of the traditional power transmission medium which existing in the sheet forming process, this paper firstly proposes a method of the sheet metal bidirectional pressure forming using a magnetorheological fluid (MRF), then the experimental device and the key structure are developed. Taking the 304 stainless steel sheet as an example, the results of the sheet metal forming under different current intensity conditions are compared. When the current intensity is increased from 0 to 4 A, the increase of the sheet forming limit reaches to 18.03 %. The maximum thinning rate of the wall thickness decreases from 28 to 22.6 %, but the forming height has an increasing trend when the punch down stroke is 15 mm. The sheets' wall thickness distribution and deformation uniformity are improved by the loading force transmission and the viscosity shear of the MRF under the gradual increased magnetic field. In conclusion, with the maturity of the process theory, it is expected to open up a new way for the study of the sheet flexible medium pressure molding process.